2016
DOI: 10.5713/ajas.16.0482
|View full text |Cite
|
Sign up to set email alerts
|

Performance and milk composition of dairy goats as affected by the dietary level of stoned olive cake silages

Abstract: ObjectiveThe current study compared the effects of dietary levels of two phase stoned olive cake (OC) in form of silage (OCS) on milk production and quality of Saanen goats.MethodsThe OCS included in total mixed ration (TMR) at dry matter proportions of 0.0 (OC0), 0.10 (OC10), and 0.20 (OC20). The TMR were fed to a total of 18 goats in a completely randomized design for a period of 5 weeks.ResultsDietary treatments had no effect on the milk yield of Saanen goats, but the daily milk fat production was greater (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
(37 reference statements)
4
12
0
1
Order By: Relevance
“…Many studies in the literature reported the absence of diet effect on goat daily milk production similarl to the present results [38]. Indeed, many authors [22][23][24]39,40] already reported the absence of OC effect as block, silage, dried and partially stoned in the diet of cows, ewes, or dairy goats. The lack of CC effect on goat milk production is in agreement with observations of Ichimura et al [20] with 20%, and Atti et al [25] and Mahouachi et al [27] with ad libitum spineless varieties of cactus.…”
Section: Milk Production and Physico-chemical Compositionsupporting
confidence: 88%
See 1 more Smart Citation
“…Many studies in the literature reported the absence of diet effect on goat daily milk production similarl to the present results [38]. Indeed, many authors [22][23][24]39,40] already reported the absence of OC effect as block, silage, dried and partially stoned in the diet of cows, ewes, or dairy goats. The lack of CC effect on goat milk production is in agreement with observations of Ichimura et al [20] with 20%, and Atti et al [25] and Mahouachi et al [27] with ad libitum spineless varieties of cactus.…”
Section: Milk Production and Physico-chemical Compositionsupporting
confidence: 88%
“…Many studies have evaluated the effect of OC on cows and ewes. To our knowledge, there are few published studies on the effects of OC [22][23][24] and cactus cladodes (CC) in the lactating goat [25][26][27]. Furthermore, no studies have investigated the effect of the incorporation of OC and CC mixture in the goats' diet.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our results, Obeidat et al [8]; CARP), Obeidat et al [16] (BB), and Janicek et al [24] (DDGS) observed no effects on milk production and composition when AF were included in the diet. Recently, Keles et al [25] supplemented dairy Saanen goats with OC silage at 0, 100, and 200 g/kg of dietary DM and observed no effect on milk yield, CP, lactose, energy corrected milk (ECM), fat corrected milk (FCM), or feed efficiency, while fat content and fat production increased. Diets containing OC silage may have produced milk with a higher fat content due to its high level of fiber (NDF and ADF) and, subsequently, more volatile fatty acids were generated (mainly acetate; the major precursor for fatty acid synthesis).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to a better utilization of the energetic quota by the lactating goats, which had the diet integrated with olive cake. Regarding milk fat yield, its value was significant higher with FWOC rationsR2 and R3than that of control one R1.Also, Keles et al (2017) mentioned that milk fat concentration increased markedly with increasing olive cake level from approximately 3.75-4.45%, presumably because of increasing dietary levels of ether extract.…”
Section: Milk Yield and Its Compositionmentioning
confidence: 93%